Da forma à imaginação, do desenho representativo, à criação de seres imaginários - Teixeira, Ana Filipa, 1978- (2017)
From an existing shape’s realistic drawing to the thinking of imaginary beings, it has a methodology which aims to demistify the act of drawing, the development of the visual language and creativity. The ocurrence and flexibilization of a creative and aesthetic thinking is a tool which allows the individual to perceive the surrounding world in a different way, as a symbolic transformation and reorganization of its being, on multiple dimensions